Environmental History in Australasia. (1st November 2004) - Robin, Libby; Griffiths, Tom
Abstract : Australia and New Zealand share a southern, settler society history and cultural solidarity as British colonies and dominions. Their early unity as 'Australasia' is where this paper begins, focusing on the strong role of science in shaping environmental history and policy in both countries. Agricultural science was crucial to environmental policy and has given a distinctive quality to the practice of environmental history in Australasia. But the long-term influences of very different physical environments and Indigenous inheritances. ultimately define Australian and New Zealand environmental historiography as more contrastive than similar, and promise to drive these countries in divergent directions.